Single-phase matrix converter using sinusoidal pulse width modulation (SPWM) / Mohd Ainor Yahya - Yahya, Mohd Ainor (2014)
A power converters incorporates an array of power switching devices that helps to convert and control electrical energy transformation under the guidance of control electronics. The general classification of converters on functional basic includes AC-DC conveters (recifier) , DC-DC converter (Chopper), DC-AC (inverter) and AC-AC converter at the same frequency (AC controller) of different frequency (Cyclo -converter) also known as matrix converter.